Biofumigation activities of volatile compounds from two Trichoderma afroharzianum strains against Fusarium infections in fresh chilies. (15th April 2021) - Khruengsai, Sarunpron; Pripdeevech, Patcharee; D'Souza, Priya E; Panuwet, Parinya
Abstract: BACKGROUND: Two Fusarium fungi, F. oxysporum and F. proliferatum, have been recognized as major pathogenic fungi that cause postharvest decay of chili fruits. Ozone and some toxic chemicals are used to control pathogenic infections, leading to longer storage lives of agricultural commodities. However, these chemicals may pose some risks to the applicators and the environment. Therefore, alternative, easy‐to‐use fumigants for effective control of Fusarium infections in harvested fresh chilies are needed. RESULTS: Two endophytic fungi, Trichoderma afroharzianum strain MFLUCC19‐0090 and T. afroharzianum strain MFLUCC19‐0091, were isolated from Schefflera leucantha leaves. Their volatile compounds were investigated for antifungal activities against F. oxysporum and F. proliferatum . In vitro results showed that the volatile compounds produced by each strain inhibited pathogen growth. Additionally, the Trichoderma ‐derived volatile compounds significantly reduced Fusarium ‐related disease severity and incidence percentages in the inoculated fresh chilies. Antifungal properties of the volatile compounds were found to be specific to the species of the tested pathogens (MFLUCC19‐0090 greatly suppressed F. oxysporum and MFLUCC19‐0091 greatly suppressed F. proliferatum ). Seventy‐three volatile compounds were detected from both strains. Among the major volatile compounds detected, phenyl ethyl alcohol was found to possess the strongest antifungal activity against both pathogens. CONCLUSION: These Trichoderma ‐derived volatile compounds may be used as alternative fumigants for controlling Fusarium rot in harvested fresh chilies. The successful use of volatile compounds as biofumigants can prevent significant market losses and, more importantly, may reduce the health hazards caused by Fusarium ‐associated mycotoxin exposures among consumers. © 2021 Society of Chemical Industry.